Digital home networking - Carbou, Romain (ISTE ; Wiley, 2011)
This much-needed book describes the digital home networking environment, its techniques, and the challenges around its service architecture. It provides a broad introduction to state-of-the-art digital home standards and protocols, as well as in-depth coverage of service architectures for entertainment and domotic services involving digital home resources. Topics include networking, remote access, security, interoperability, scalability, and quality of service. Notably, the book describes the generic architecture that was proposed and developed in the context of the EUREKA/Celtic research project Feel@Home.